Fracture risk reduction and safety by osteoporosis treatment compared with placebo or active comparator in postmenopausal women: systematic review, network meta-analysis, and meta-regression analysis of randomised clinical trials. (2nd May 2023) - Händel, Mina Nicole; Cardoso, Isabel; von Bülow, Cecilie; Rohde, Jeanett Friis; Ussing, Anja; Nielsen, Sabrina Mai; Christensen, Robin; Body, Jean-Jacques; Brandi, Maria Luisa; Diez-Perez, Adolfo; Hadji, Peyman; Javaid, Muhammad Kassim; et al.
Abstract: Objective: To review the comparative effectiveness of osteoporosis treatments, including the bone anabolic agents, abaloparatide and romosozumab, on reducing the risk of fractures in postmenopausal women, and to characterise the effect of antiosteoporosis drug treatments on the risk of fractures according to baseline risk factors. Design: Systematic review, network meta-analysis, and meta-regression analysis of randomised clinical trials. Data sources: Medline, Embase, and Cochrane Library to identify randomised controlled trials published between 1 January 1996 and 24 November 2021 that examined the effect of bisphosphonates, denosumab, selective oestrogen receptor modulators, parathyroid hormone receptor agonists, and romosozumab compared with placebo or active comparator. Eligibility criteria for selecting studies: Randomised controlled trials that included non-Asian postmenopausal women with no restriction on age, when interventions looked at bone quality in a broad perspective. The primary outcome was clinical fractures. Secondary outcomes were vertebral, non-vertebral, hip, and major osteoporotic fractures, all cause mortality, adverse events, and serious cardiovascular adverse events. Results: The results were based on 69 trials (>80 000 patients). For clinical fractures, synthesis of the results showed a protective effect of bisphosphonates, parathyroid hormone receptor agonists, and romosozumab compared with placebo. Compared with parathyroid hormone receptor agonists, bisphosphonates were less effective in reducing clinical fractures (odds ratio 1.49, 95% confidence interval 1.12 to 2.00). Compared with parathyroid hormone receptor agonists and romosozumab, denosumab was less effective in reducing clinical fractures (odds ratio 1.85, 1.18 to 2.92 for denosumab v parathyroid hormone receptor agonists and 1.56, 1.02 to 2.39 for denosumab v romosozumab). An effect of all treatments on vertebral fractures compared with placebo was found. In the active treatment comparisons, denosumab, parathyroid hormone receptor agonists, and romosozumab were more effective than oral bisphosphonates in preventing vertebral fractures. The effect of all treatments was unaffected by baseline risk indicators, except for antiresorptive treatments that showed a greater reduction of clinical fractures compared with placebo with increasing mean age (number of studies=17; β=0.98, 95% confidence interval 0.96 to 0.99). No harm outcomes were seen. The certainty in the effect estimates was moderate to low for all individual outcomes, mainly because of limitations in reporting, nominally indicating a serious risk of bias and imprecision. Conclusions: The evidence indicated a benefit of a range of treatments for osteoporosis in postmenopausal women for clinical and vertebral fractures. Bone anabolic treatments were more effective than bisphosphonates in the prevention of clinical and vertebral fractures, irrespective of baseline risk indicators. Hence this analysis provided no clinical evidence for restricting the use of anabolic treatment to patients with a very high risk of fractures. Systematic review registration: PROSPERO CRD42019128391.